Zone of influence for particle number concentrations at signalised traffic intersections. (December 2015) - Goel, Anju; Kumar, Prashant
Abstract: Estimation of zone of influences (ZoI) at signalised traffic intersections (TI) is important to accurately model particle number concentrations (PNCs) and their exposure to public at emission hotspot locations. However, estimates of ZoI for PNCs at different types of TIs are barely known. We carried out mobile measurements inside the car cabin with windows fully open for size–resolved PNCs in the 5–560 nm range on a 6 km long busy round route that had 10 TIs. These included four–way TIs without built–up area (TI4w-nb ), four–way TIs with built–up area (TI4w-wb ), three–way TIs without built–up area (TI3w-nb ) and three–way TIs with built–up area (TI3w-wb ). Mobile measurements were made with a fast response differential mobility spectrometer (DMS50). Driving speed and position of the car were recorded every second using a global positioning system (GPS). Positive matrix factorisation (PMF) modelling was applied on the data to quantify the contribution of PNCs released during deceleration, creep–idling, acceleration and cruising to total PNCs at the TIs. The objectives were to address the following questions: (i) how does ZoI vary at different types of TIs in stop– and go–driving conditions?, (ii) what is the effect of different driving conditions on ZoI of a TI?, (iii) how realistically can the PNC profiles be generalised within a ZoI of a TI?, and (iv) what is the share of emissions during different driving conditions towards the total PNCs at a TI? Average length of ZoI in longitudinal direction and along the road was found to be the highest (148 m; 89 to −59 m from the centre of a TI) at a TI3w-wb, followed by TI4w-nb (129 m; 79 to −42 m), TI3w-nb (86 m; 71 to −15 m) and TI4w-wb (79 m; 46 to −33 m) in stop– and go–driving conditions. During multiple stopping driving conditions when a vehicle stops at a TI more than once in a signal cycle due to oversaturation of vehicles, average length of ZoI increased by 55, 22 and 21% at TI4w-nb, TI3w-nb and TI3w-wb, respectively, compared with stop– and go–driving conditions. Within average length of ZoI in stop– and go– driving conditions, PNCs followed a three degree polynomial form at all TIs. Dimensional analysis suggested that coefficients of polynomial equations at both four–way and three–way TIs were mainly influenced by delay time, wind speed and particle number flux. The PMF analysis suggested that deceleration contributed the most to total PNCs at all TIs, except TI4w-wb . Findings of this study are a step forward to understand the contribution of different driving conditions towards the total PNCs and their exposure at the TIs. Graphical abstract: Highlights: On–road particle number concentration (PNC) measured at traffic intersections (TI). Dimensional analysis showed reliance of PNC profiles on delay time at four-way TIs. Zone of influence depends on idling time and PNCs within them on vehicle speed. Three degree polynomial distribution represented the PNC profiles well at all TIs. PMF results showed deceleration to contribute maximal PNCs at all intersections.